Innovations in Short Video Marketing Strategies for Tourism: The Case of The Director of Garzê Culture and Tourism Bureau - Li, Han; Tay, KaiXin (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Short tourism videos (STVs) can significantly boost the visibility and appeal of tourist destinations, increase tourism revenue, and yield positive social responsibility effects such as poverty alleviation. One notable achievement is that of Liu Hong, the Director of the Culture and Tourism Bureau in Garzê , who has become an Internet celebrity by successfully promoting Garzê 's cultural and tourism resources via his TikTok account with 156 STVs. This study aims to analyze and uncover the characteristics of effective STVs in promoting sustainable tourism and conservation. The STVs were classified into four narrative categories: recommendation-based, introduction-based, display-based, and activity-based. The findings revealed that among the 25 highly engaged STVs, display-based STVs were dominant, accounting for 68%. Comparing short video length, number of scenes, subtitles, background music, and number of characters in association with engagement metrics, revealed that display-based STVs are usually less expensive and require fewer resources to produce. This suggests that destination management organizations can leverage display-based STVs to engage netizens and promote tourist destinations. These findings help promote remote tourism destinations with smaller marketing budgets, fostering sustainable tourism practices, and conserving natural and cultural heritage. The study helps DMOs aiming to use STVs for effective and sustainable destination marketing.